2017
DOI: 10.1007/s11010-017-3167-x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of aryl acylamidase activity of acetylcholinesterase in osteoblast differentiation and mineralization

Abstract: Osteoblast differentiation is an essential event in the developmental process, which is favoured by the production of extra cellular matrix proteins and various enzymes including discrete ones like acetylcholinesterase (AChE). Despite the fact that AChE facilitates osteoblast differentiation, the significance of its catalytic functions [esterase and aryl acylamidase (AAA) activities] in the process is yet to be ascertained. In this context, SaOS-2 cell line was used in the present study to implicate the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The expression pattern in the bone tissue of the ancestrally exposed individuals suggested an inhibited osteoblastogenesis event during skeletogenesis possibly responsible for the significantly reduced osteoblast number. Both ACHE (down-regulated) and TP53INP2 (down-regulated) play a role in facilitating osteoblast differentiation and mineralization in vitro by activating Wnt/β-catenin signalling [ 69–71 ]. LRP3 , an LRP family member, was found to be inhibited and possibly indicative for reduced osteogenesis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern in the bone tissue of the ancestrally exposed individuals suggested an inhibited osteoblastogenesis event during skeletogenesis possibly responsible for the significantly reduced osteoblast number. Both ACHE (down-regulated) and TP53INP2 (down-regulated) play a role in facilitating osteoblast differentiation and mineralization in vitro by activating Wnt/β-catenin signalling [ 69–71 ]. LRP3 , an LRP family member, was found to be inhibited and possibly indicative for reduced osteogenesis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…AChE has three variants known as AChE-S, AChE-R, and AChE-E and they have multiple biological effects [39]. Previous studies showed that AChE was related to neuronal differentiation and mineralization, as well as extension of neurite outgrowth [40,41]. In addition, AChE activity is not limited to cholinergic transmission and is associated with several non-cholinergic actions such as cell proliferation [42].…”
Section: Discussionmentioning
confidence: 99%
“…In older literature, such enzymes were generally referred to as aryl acylamidases (AAAs). Moreover, AAA side activities were described for acetylcholinesterase [ 46 ], also under the name of AAA-2 [ 47 ], and butyrylcholinesterase [ 48 , 49 , 50 ], but their roles as melatonin-converting enzymes seem to be low or irrelevant. Other AAAs were detected in liver [ 51 , 52 ], brain [ 47 ] and pineal gland [ 53 ].…”
Section: The Deacetylation Pathwaymentioning
confidence: 99%